The Role of Social Physique Anxiety in Determining the Motivation for Participating in Physical Activity - Javad Salehi; Ahmad Rahmani (University of Tehran, 2010)
Research suggests that people with high anxiety about their body shape participate in exercise less than others, and in the case of participation, their main motivation is internal motivation. Considering the prevalence of social physique anxiety and its strong negative influence on the motivation to participate in physical activity, it is necessary to study the effect of this factor and its interaction with the personality characters to determine the motivation to participate in physical activity. Thus, the aim of the present study was to investigate the effect of social physique anxiety (SPA) on the kind of motivation for exercise, and to determine intervening role of self-esteem. For this purpose, a sample of 265 undergraduate students of Zanjan Univeristy (156 females and 109 males) were randomly selected and completed a booklet consisting of "Social physique anxiety scale", "Rosenberg self-esteem scale", "sport motivation scale" and demographic information. The results of the study revealed that external motivation for exercise was higher in students with high SPA than those with low SPA (P=0.017). Lack of motivation was higher in students with high SPA than others (P = 0.008). In addition, it was observed that there was a significant interaction between SPA and self-esteem if affecting exercise motivation was concerned (P = 0.019). In conclusion, the present study indicated that SPA had an important role in determining the kind of motivation for participation in physical activity.